Skin infiltrating NK cells in cutaneous T-cell lymphoma are increased in number and display phenotypic alterations partially driven by the tumor - Scheffschick, Andrea; Nenonen, Julia; Xiang, Mengmeng; Winther, Anna H.; Ehrström, Marcus; Wahren-Herlenius, Marie; Eidsmo, Liv; Brauner, Hanna (Frontiers in Immunology, 2023)
Cutaneous T cell lymphomas (CTCL) are characterized by focal infiltration of malignant T cell clones in solitary skin lesions. Many CTCL patients experience an indolent disease, but some progress to advanced disease with high fatality. We hypothesized that natural killer (NK) cells participate in local control of tumor growth in CTCL skin. Immunohistochemistry and flow cytometry analysis of the density, localization, phenotype and function of NK cells in twentynine fresh or formalin-fixed skin biopsies from twenty-four CTCL patients and twenty-three biopsies from twenty healthy controls highlighted higher numbers of CD56 + CD3 -NK cells in CTCL skin. A reduced fraction of CTCL skin NK cells expressed the maturation marker CD57, the cytotoxic protein granzyme B and the activation marker CD69, indicating reduced tumor-killing abilities of the NK cells. Retained expression of immune checkpoint proteins or inhibitory proteins including PD1, TIM3, LAG3, CD73 and NKG2A and the activating receptors CD16 and NKp46 indicated maintained effector functions. Indeed, the capacity of NK cells to produce anti-tumor acting IFNγ upon PMA+ionomycin stimulation was similar in cells from CTCL and healthy skin. Co-cultures of primary human NK cells or the NK cell line NKL with CTCL cells resulted in reduced levels of granzyme B and CD69, indicating that close cellular interactions with CTCL cells induced the impaired functional NK cell phenotype. In conclusion, increased numbers of NK cells in CTCL skin exhibit a partially impaired phenotype in terms of activity. Enhancing NK cell activity with NK cell activating cytokines such as IL-15 or immune checkpoint blockade therefore represents a potential immunotherapeutic approach in CTCL.